G334(P) Early Outcome of Directly Observed Treatment, Short Course (DOTS) strategy for Childhood Tuberculous Meningitis: Analysis from a Tertiary Centre in India. (7th April 2014) - Dewan, P; Chadha, TK; Kaur, IR; Gupta, P
Abstract : Aim: We evaluated the early outcome of intermittent Directly Observed Therapy – Short course (DOTS), for children admitted with tuberculous meningitis (TBM) treated under the National TB Control Program in Delhi, India. Methods: Participants : 30 children with TBM. Those with pre-existing neurological disorders and mental retardation were excluded. Design : Prospective observational. Setting : Inpatients, tertiary hospital. Intervention : Diagnosis was based on clinical features, characteristic CSF and neuroimaging findings, and supportive evidence of tuberculosis (contact, abnormal chest radiograph, and positive tuberculin test). Participants received anti-tuberculous drugs thrice a week (2H3 R3 Z3 E3 + 7H3 R3 ) in addition to supportive therapy. Outcome variables: Mortality and neurological morbidity within 8 weeks of starting anti-tuberculous therapy. Results: We evaluated 30 children with TBM aged 10 months to 12 years. At the end of 8 weeks of treatment, the overall mortality was 40% (12/30). All children who expired had Stage 3 TBM at admission. Of the survivors (n = 18), 9 (50%) had significant neurological morbidity (spasticity 2, cranial neuropathy 6, visual deficit 4, motor deficit 7). A significant correlation existed between mortality and lack of BCG vaccination (r = 0.6, p < 0.001), younger age (r = 0.39, p = 0.03), stunting (r = 0.44, p = 0.014), wasting (r = 0.52, p = 0.004) and increasing severity of the disease (r = 0.53, p = 0.001). Conclusion: Intermittent short course directly observed therapy (DOTS) for children with tuberculous meningitis is associated with a high early mortality and significant neurological morbidity after 8 weeks of therapy under program conditions in India. There is a need to compare it with regimes of daily therapy.